Widespread occurrence of N(6)-methyladenosine in bacterial mRNA - Deng, Xin (Nucleic Acids Res, 2015)
N(6)-methyladenosine (m(6)A) is the most abundant internal modification in eukaryotic messenger RNA (mRNA). Recent discoveries of demethylases and specific binding proteins of m(6)A as well as m(6)A methylomes obtained in mammals, yeast and plants have revealed regulatory functions of this RNA modification. Although m(6)A is present in the ribosomal RNA of bacteria, its occurrence in mRNA still remains elusive. Here, we have employed ultra-high pressure liquid chromatography coupled with triple-quadrupole tandem mass spectrometry (UHPLC-QQQ-MS/MS) to calculate the m(6)A/A ratio in mRNA from a wide range of bacterial species, which demonstrates that m(6)A is an abundant mRNA modification in tested bacteria. Subsequent transcriptome-wide m(6)A profiling in Escherichia coli and Pseudomonas aeruginosa revealed a conserved m(6)A pattern that is distinct from those in eukaryotes. Most m(6)A peaks are located inside open reading frames and carry a unique consensus motif of GCCAU. Functional enrichment analysis of bacterial m(6)A peaks indicates that the majority of m(6)A-modified genes are associated with respiration, amino acids metabolism, stress response and small RNAs, suggesting potential functional roles of m(6)A in these pathways.